Comparative evaluation QoS of FTP over LEO and GEO satellite networks with diffserv architecture - Audah, Lukman; Sun, Zhili; Cruickshank, Haitham (David publishing, 2012)
This paper presents studies of the end-to-end QoS of IP over integrated terrestrial and NGSN (next generation satellite network) for file transfer service using FTP. The authors compare between LEO and GEO satellites constellations for the QoS parameters (i.e., delay, jitter, loss rate and throughput) of file transfer between one server in London and a client in Boston. The authors model the file transfer with multiple connections and file size variation according to exponential and Pareto distributions respectively. The authors create the scenario with error model to simulate transmission loss environment using the NS-2 simulation software. A Diffserv (differentiated services) queue interface is placed in the server side to regulate the traffic flows across the narrow bandwidth of the satellite links. The authors compare the empirical TCP throughput traces with analytical model for validation. The results showed the performance evaluation and presented a good comparison of the QoS parameters involved in the data transfer across LEO and GEO satellites systems.